PENERAPAN METODE RESITASI NAMA ILMIAH PADA MATERI KEANERAGAMAN HAYATI SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR SISWA - maryam, siti (Jurnal Penelitian dan Penilaian Pendidikan, 2024)
This research is motivated by the importance of student learning successas an effort to obtain quality output. Some of the elements involved in schoolinstitutions include school principals, teachers, TU staff, and students. From theseelements, teacher competence in using interesting learning methods is one of theimportant aspects to achieve this goal. The problems identified in learningbiology are: There is an assumption that Biology is quite difficult, because thereare lots of memorization and terms; Lack of interest and motivation in learningabout Biology subjects; Lack of use of appropriate learning techniques, methodsand media by teachers; Student learning outcomes on daily tests are still low.Therefore, this research is focused on the formulation of the problem How is theeffect of applying the method of reciting scientific names with binomial nomenclature to increasing students' cognitive competence? ; How does theapplication of the scientific name recitation method with binomial nomenclatureaffect the increase in students' affective competence? The purpose of this studywas to obtain data and facts regarding the effect of applying the scientific namerecitation method with binomial nomenclature by increasing students' cognitivecompetence; obtain data and facts regarding the effect of applying the scientificname recitation method with binomial nomenclature by increasing students'affective competence. This research was carried out in 2 cycles with the planningstage, the acting stage, the observation stage, and the reflection stage. In thisstudy, the recitation method was considered to be significant in increasingstudents' learning outcomes.